Tindak Pidana Penganiayaan yang Menyebabkan Kematian Perspektif Hukum Positif dan Hukum Pidana Islam - Moh Alviyan (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Persecution is one of the offenses that are the focus of discussion in both positive and Islamic criminal law, the purpose of this study itself is to explain the similarities and differences in the judgments of the torture law that cause death in the perspective of Islamic criminal law and positive criminal law. Persecution that results in death is likened to the deliberate murder of the wrongdoer (qatl al-khata ') who is punished by kifarah. However, it is different from the positive law that applies in Indonesia, in articles 351-358 of the Criminal Code, it is clear about the punishment for perpetrators of persecution. It is undeniable that the two existing legal systems both punish the perpetrator of a criminal act of torture that causes death, but in terms of the method for positive law it places more emphasis on the prison law while in jinayah there is no prison sentence for the perpetrator. The type and nature of research used in this research is the type of library research to examine through books, books and scientific works related to the problem, as well as being descriptive, analytic and comparative.